Trematodosis pada Sapi yang Disembelih di Rumah Potong Hewan Kabupaten Manokwari Propinsi Papua Barat - Purwaningsih, Purwaningsih; Nurhayati, Dwi (Jurnal Veteriner, 2022)
Trematodosis is one of economic disease caused by worm parasitic from group of trematode and their distribution found widespread on farm and livestock.  This study  was aim to determine the prevalence, distribution, and risk factor of trematodosis in livestock in Manokwari, West Papua abattoir.  Study was conducted on March until May 2018. Fresh sample feces were taken from 99 cattles per rectal in Manokwari abattoir with purposive sampling method. Samples examined with filtration and sedimentation modification method to identify the existence of egg trematode based on their morphology. Trematodosis prevalence obtained by analyzing data in univariate, and bivariate analysis used to examine trematodosis risk factor by chi-square test (?2) and odds ratio (OR).  The overall trematodosis prevalence in livestock in Manokwari abattoir were 52.53%, with the trematode found were 34.34% Fasciola spp., and 42.42% Paramphistomum spp.  Predisposing factors such as sex and season were not statistically significant association (P>0.05) with trematodosis prevalence of cattle in Manokwari abattoir. However, there was a statistically signifant association of trematodosis prevalence between age group (P<0.05), with odds ration 2.996.  Risk factor that play a role in the incidence of trematodosis is the age of livestock over two years.